2001
DOI: 10.1159/000047339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Heart Disease in Asymptomatic Chronic Cocaine Users

Abstract: To determine the prevalence of heart disease in outpatient young asymptomatic chronic cocaine users, 35 cocaine users and 32 age-matched controls underwent resting and exercise electrocardiography (ECG) and Doppler echocardiography. Findings consistent with coronary artery disease were detected in 12 (34%) patients and 3 (9%) controls (p = 0.01). Decreased left ventricular systolic function was demonstrated in 5 (14%) patients, but in none of the controls (p = 0.055). Finally, resting and peak exercise abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…We also observed global LV systolic dysfunction in 34% of our series. This prevalence was higher than in previous echocardiographic reports on asymptomatic patients, in which it ranged from 0% to 14% [7,13,32,36]. Still, we only found mild systolic dysfunction, with the lowest LVEF being 48%, probably because we assessed the chronic effect of cocaine and not the acute phase effect, and also because our cocaine abusers were asymptomatic and likely to have less severe cardiac involvement.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…We also observed global LV systolic dysfunction in 34% of our series. This prevalence was higher than in previous echocardiographic reports on asymptomatic patients, in which it ranged from 0% to 14% [7,13,32,36]. Still, we only found mild systolic dysfunction, with the lowest LVEF being 48%, probably because we assessed the chronic effect of cocaine and not the acute phase effect, and also because our cocaine abusers were asymptomatic and likely to have less severe cardiac involvement.…”
Section: Discussioncontrasting
confidence: 72%
“…Overall, some degree of cardiac involvement was shown in 71% of CA, and LV dysfunction was related to number of years of regular cocaine use, which may have practical importance in these patients’ medical care. It has been previously shown that cocaine is cardiotoxic in both symptomatic [32] and asymptomatic [13,33] CA, but, as far as we are aware, this is the first comprehensive study to assess with CMR cocaine cardiac and vascular toxicity in a reasonably large cohort of consecutive, non-selected, asymptomatic CA, comparing LV and RV results to healthy age and gender matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyopathy due to myocardial siderosis has been reported in other patients with iron overload due to sideroblastic anemia [23]. Cocaine use, reported by the present patient, increases the risk of left ventricular dysfunction, myocardial infarction and other manifestations of heart disease [24, 25]. This accounts for his myocardial infarction at presentation, and may have exacerbated his cardiomyopathy.…”
Section: Discussionsupporting
confidence: 55%
“…Myocardial dysfunction is common in young asymptomatic chronic cocaine users. In one study, 14% of young chronic cocaine users had decreased LV systolic function by echocardiography and more than a third had abnormal LV filling during exercise testing [17]. It is also interesting to speculate whether cocaine abuse contributed to the development of hypopituitarism.…”
Section: Discussionmentioning
confidence: 99%